Circular Economy Integration in the Daulat Sampah Program by Stakeholders in Trisik Beach, Yogyakarta - Sasongko, Yohanes Probo Dwi; Haryono, Cosmas Gatot; Herlina, Herlina (Humaniora: Journal of Indonesia Culture and Society, 2025)
The waste problem at Trisik Beach in Yogyakarta Province remains a complex and urgent issue that requires immediate attention. Addressing this environmental challenge while supporting economic growth in coastal ecosystems necessitates ongoing collaborative efforts. The Banaran Tourism Awareness Group (Pokdarwis), along with local artists and other stakeholders, has initiated a social activity focused on environmental cleanliness called Daulat Sampah. This program promotes sustainable practices and applies the circular economy concept, where waste is recycled into artworks that possess both aesthetic and commercial value. This not only contributes to the economic development of the Banaran community but also serves as a model for environmental improvement through the reuse of materials. Joint actions, such as waste reduction and reuse, function as community education tools, fostering greater awareness and concern for the surrounding environment. This research employs field observations, in-depth interviews, and literature reviews, with data analyzed descriptively and qualitatively. The findings suggest that adopting the circular economy concept offers a viable solution for integrated environmental management. The structuring process within this program shows potential to mitigate ecological damage caused by recent weather changes. Moreover, waste management activities at this marine tourism site exemplify practical sustainable development. Such initiatives can be implemented comprehensively across various marine tourism sites, especially along the southern coastal region of Java Island.